Needs Analysis of Blended Learning Development on Instructor Training at Basarnas - Abdillah, Adi; Solihatin, Etin; W, R.A Murti Kusuma (Journal of Education Research and Evaluation, 2020)
Blended learning facilitates learning by providing various learning resources and considering the characteristics of learners. This study aims to conduct a needs analysis for the development of blended learning in instructor training at Basarnas. Needs analysis is carried out to explore information about gaps and needs as well as student profiles that can be used as a basis or reference in developing blended learning at the next stage. This research is a descriptive study with quantitative approach. Data collection was carried out by means of observation, interviews, and distributing questionnaires. Interviews were conducted with the Head of the Sub-Directorate for Planning and Standardization of Basarnas Personnel, while the filling of the questionnaire was carried out by the Basarnas Rescuer who will attend instructor training as many as 50 respondents. The results show that instructor training at Basarnas can be designed in the form of blended learning by using a project-based learning approach to overcome existing limitations or gaps so that the implementation of blended learning that combines the delivery of face-to-face learning and online learning can be an intervention that is suitable to be applied and appropriate. with the needs at Basarnas.